More and More Academics and Not Enough Skilled Workers - Karl Brenke (Wirtschaftsdienst)
Abstract All western countries are faced with the problem of a low birth rate and an increasingly aging population. The burden of old age requires accelerated productivity growth. Productivity growth is declining, however. In Germany, it has come to a standstill. At the same time, there is an increasing academisation of the labour force. There are several reasons for this paradox: sectoral change or bureaucratisation. A shortage of qualified blue collar workers is also a contributing factor.